2017
DOI: 10.15252/embj.201696025
|View full text |Cite
|
Sign up to set email alerts
|

A G1‐like state allows HIV ‐1 to bypass SAMHD 1 restriction in macrophages

Abstract: An unresolved question is how HIV‐1 achieves efficient replication in terminally differentiated macrophages despite the restriction factor SAMHD1. We reveal inducible changes in expression of cell cycle‐associated proteins including MCM2 and cyclins A, E, D1/D3 in macrophages, without evidence for DNA synthesis or mitosis. These changes are induced by activation of the Raf/MEK/ERK kinase cascade, culminating in upregulation of CDK1 with subsequent SAMHD1 T592 phosphorylation and deactivation of its antiviral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(147 citation statements)
references
References 60 publications
(73 reference statements)
9
138
0
Order By: Relevance
“…To test this, we treated MDM with 5 μM ETO, infected cells with HIV‐1 and assayed phosphorylation of SAMHD1 at T592 by immunoblot (Fig A–C). We found that SAMHD1 is phosphorylated in untreated MDM allowing efficient HIV infection, confirming previous data (Mlcochova et al , ). Addition of ETO led to loss of SAMHD1 phosphorylation and reduced HIV‐1 infectivity.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…To test this, we treated MDM with 5 μM ETO, infected cells with HIV‐1 and assayed phosphorylation of SAMHD1 at T592 by immunoblot (Fig A–C). We found that SAMHD1 is phosphorylated in untreated MDM allowing efficient HIV infection, confirming previous data (Mlcochova et al , ). Addition of ETO led to loss of SAMHD1 phosphorylation and reduced HIV‐1 infectivity.…”
Section: Resultssupporting
confidence: 92%
“…In the absence of type I IFN related changes we were able to demonstrate that the ETO‐induced block is mediated by SAMHD1 T592 phosphorylation. Activation of p53 and the downstream p21 lead to decreased expression of CDK1, the key kinase in SAMHD1 phosphorylation (Cribier et al , ; Mlcochova et al , ). As expected from our previous data this loss of CDK1 activity and SAMHD1 phosphorylation was associated with transition of G1‐like MDM back into G0 state without induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of the enzyme is mediated by the presence of a putative cyclin-binding motif located in the HD domain (residues 450–455), as well as a bipartite cyclinA2-CDK complex binding motif located in the C-terminus (99, 118). Further investigation of this regulatory axis reveals that SAMHD1 phosphorylation likely occurs as cells emerge from a G 0 /quiescent state and transition through G 1 facilitated by a mitogen induced activation of the Raf/MEK/Erk kinase cascade (122). Conversely, for cells residing in a non-cycling G 0 /quiescent state, multiple studies report that the dephosphorylated SAMHD1 species predominates and corresponds with reduced dNTP levels (98, 99, 117).…”
Section: Samhd1 Cellular Regulation and Nucleotide Metabolismmentioning
confidence: 99%
“…21: e47528 | 2020 ª 2019 The Authors cells using shRNA(Fig EV1A)or full knockout cells using the CRISP-Cas9 technology (CRISP-Cas9-TRIM21,…”
mentioning
confidence: 99%